A influência do imaginário europeu nas representações sobre os nativos da América portuguesa: uma análise dos escritos do padre Fernão Cardim - Chaves, Romildo Pereira (2009)
This work examines the construction of the images on Brazilian natives created by the Portuguese Jesuit Fernão Cardim, approaching the Christian look in the 16th century. The primary objective is to observe and note the outstanding presence of the ideas and values of the medieval world on Brazil in Father Fernão Cardim s work, aiming to detect permanences and changes in a study that focuses the long duration. The theoretical and methodological course is anchored in the perspective of ethnocentrism and of imaginary, considering them as a category, object of knowledge and fact in the world. The imaginary and the ethnocentric attitude are predominant factors in the construction, legitimation and justification of actions by the Jesus Company and the Portuguese State toward the people who lived in 16th century Brazil. This ethnocentric imaginary persisted in Brazilian history and one often observes actions, attitudes and positions that carry an inheritance of this way of thinking the Brazilian indigenous peoples. The research was based on Le Goff s theoretical assumptions and was supported by anthropological analyses on the indigenous reality. The approach starts from the analysis of Father Fernão Cardim s writings and the permanence of an ethnocentric look on the indigenous